Modified habitat use by tropical forest dependent birds in the Caribbean region of Guatemala - Cerezo, Alexis (2009)
As natural areas are reduced into isolated remnants, the importance of secondary habitats for species conservation will increase. Consequently, the conservation value of human-modified or created secondary habitats must be determined. In this study, we evaluated the conservation potential of three habitats associated to cattle ranching (riparian forest, live fence, and pasture) for tropical forest birds in the Caribbean region of Guatemala. We studied the bird communities of five tropical forest and riparian forest (henceforth river) sites, three live fence sites and four pasture sites, in five cattle ranches in the region, and compared the four habitats based on the following parameters: species richness, number of individuals, species composition and an index of con- servation importance. A 10-point series was sampled (six repetitions of each series) in each habitat site using the point-count method, in march and april of 1998 and 1999. Although forest, river and live fence had similar mean species numbers, considering all species (111, 96 and 94 species, respectively), and river and live fence surpassed the forest in mean number of individuals (80 and 72 compared to 56 individuals), river and live fence had significantly fewer mean numbers of interior-forest resident species and individuals (56, 21 and 15 species, and 61, 19 and eight individuals in forest, river and live fence, respectively). River and live fence, when com- pared to forest, had no significant differences in the number of resident forest edge species and individuals, but their edge species composition was significantly different from forest. Those resident edge species that were relatively abundant in forest had very low abundances in the modified habitats, and those that were abundant in river and live fence were rare or absent in forest sites. With respect to migratory species, both river and live fence were very important, and the river was more important than forest, according to the conservation importance index. We conclude that these modified habitats have very little value for tropical forest-dependent resident species, but are extremely important for migratory species, particularly those of arboreal habits. We also stress that the conservation importance of alternative habitats should be based on species composition, as opposed to species richness and abundance, and defined as a function of species of particular conservation importance, in our locality, those dependent of tropical lowland forest.